The Effectiveness of the Aswat Arabiyah Strategy in Improving Imla' Learning Outcomes for Class VIII MTs Al-Jauhar Duri - Mohd Fikri Azhari; Indah Sari; Henrizal Hadi (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
The purpose of this study was to determine the application of the Ashwat Arabiyah strategy in learning Imla 'to improve the writing skills of class VIII students at MTs Al-Jauhar Duri and to find out the improvement in the achievement results of class VIII students at MTs Al-Jauhar Duri in Arabic writing skills after receiving the Ashwat Arabiyah strategy. This research was conducted at Pondok Modern Al-Jauhar Duri, Jalan Asrama Tribrata, Pematang Pudu Village, Mandau District, Bengkalis Regency. The sample used was 1 Imla' teacher and 26 students of class VIII.C. This study uses a classroom action research design (PTK), which is research conducted in the classroom by observing activities that are intentionally raised and occur in a class. The research procedure consists of planning, implementing, observing, and reflecting. Based on the results, it is known that the initial condition of the ability of class VIII MTs Al-Jauhar Duri in learning Imla 'is low, most of them have not been able to distinguish hijaiyah letters and connect them in a sentence. This is evidenced by the results of the pre-cycle average ability of 11, 53% of students. Meanwhile, the writing ability in learning Imla' Class VIII MTs Al-Jauhar Duri can be improved by using the Ashwat Arabiyah strategy, this is evidenced from the results of the pre-cycle the average ability of students is 11.53%, in the first cycle the average ability of students is 15,38%, in the second cycle the average ability of students is 65.38%, and in the third cycle the average ability of students is 73.07%. This shows that there is a positive impact from the implementation of the Ashwat Arabiyah strategy in improving the writing ability of VIII grade students at MTs Al-Jauhar Duri with an indicator of success in cycle III as much as 73.07%.